Agricultural cooperative system: management challenges and feasible solutions - Oliveira Junior, Osmar de Paula; Wander, Alcido Elenor (Revista de Administração da UFSM, 2022)
Purpose/objective: To describe the managerial challenges agricultural cooperatives face and list the leading solutions that can be adopted to overcome such bottlenecks. Design/methodology/approach: A systematic literature review was done, with a research protocol based on “Methodi Ordinatio” (Pagani et al., 2015) to select relevant papers. The study covered aspects of management and administration of agro-industrial cooperatives, social management, risk management in agribusiness, strategic management in agribusiness, new generation cooperatives, cooperative management, cooperative governance and challenges to the cooperative system. Findings: Efficient conciliation of cooperatives’ social and economic agenda requires management professionalization. The cooperative must adopt a series of good management and governance practices and a strategic positioning that guarantees a competitive position, putting it on an equal footing with private firms. The central management tools identified are separation between control and ownership, strategic management, strategic alliances and partnerships, management branding, restricted membership, social management, self-financing and risk management, with numerous other management options available. The main obstacles are the conservative environment and the need to update cooperative doctrinal principles, impediments to modernizing Brazilian agricultural cooperatives’ management. Originality/value: The paper identifies aspects of a conservative environment and the need to update the cooperative principles that hinder the modernization of the management in Brazilian agricultural cooperatives.